Investigation Of Physical And Chemical Properties Of Spent Bleaching Clay Based Geopolymers Using Alkaline Activated Geopolymerization Process - Mak, Wei Ying (2023)
This research explores the synthesis and characterization of porous clay-based geopolymers using uncalcined spent bleaching clay (SBC) as a novel precursor. Geopolymers, celebrated for their mechanical strength and chemical durability, have traditionally been synthesized using fly ash or calcined kaolin clay. The problem statement arises from the extensive potential of SBC, a waste product from the palm oil refining industry rich in aluminosilicate material, which is often discarded in landfills. The study's overarching aim is to optimize the geopolymerization process for both SBC-based and calcium silicate-SBC based geopolymers. Depending on the design parameters, geopolymer can be produced with various properties and advantages, such as excellent strength and thermal resistance under acidic environment. The result showed that a mass ratio of NaOH to Na2SiO3 of 3.50, mass ratio of alkaline activator solution to SBC of 2.25, and a utilization of 10% CS has the best condition. In this study, the geopolymer paste was cured in an oven at 80℃ for 24h and at room temperature for 7 days. Characterization efforts encompass an extensive analysis of raw materials, including SBC and calcium silicate, and the synthesized porous geopolymers, evaluating their structural, mechanical, thermal, and chemical properties. The characterization included FTIR spectroscopy, SEM/EDX, TGA, BET, XRD, and compressive strength test.